Penerapan Kitab Tuhfatul Athfal pada Hukum Tajwid dalam Meningkatkan Kemampuan Membaca Al-Qur’an - Citra Ramai Yanti; Ahmad Sopian; Muhammad Roihan Alhaddad (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The Qur'an serves as the primary guidance for Muslims in achieving well-being in this world and the hereafter. Therefore, it must be recited correctly, as incorrect pronunciation may alter its intended meaning. Tajweed is the discipline that governs proper Qur'anic recitation. This study aims to examine the implementation of the Tuhfatul Athfal book in teaching tajweed and to evaluate its effectiveness in improving the Qur'an reading skills of eighth-grade students at SMP IT Al-Mumtaazah Pedamaran. This research employed a descriptive qualitative method. Data were collected from Qur'an and Tahfidz teachers as well as eighth-grade students through observation, interviews, and documentation. Primary data were obtained directly from participants, while secondary data were gathered from relevant literature and journals. Data were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Tuhfatul Athfal book was carried out systematically through several learning activities, including reciting the nadzham together at the beginning of each lesson, explaining tajweed rules, demonstrating the correct pronunciation of makhraj letters, and practicing Qur'anic recitation according to the tajweed principles studied. These activities enabled students to understand and apply the rules of tajweed more effectively. Furthermore, the use of the Tuhfatul Athfal book proved effective in improving students' Qur'an reading skills. It facilitated memorization of fundamental tajweed rules, enhanced students' comprehension of tajweed concepts, and supported a gradual and structured learning process. Overall, the Tuhfatul Athfal book serves as an effective instructional medium for strengthening tajweed mastery and improving the quality of Qur'anic recitation among junior high school students.